Optical studies of two stripped-envelope supernovae – SN 2015ap (Type Ib) and SN 2016P (Type Ic). Issue 3 (7th July 2020) - Gangopadhyay, Anjasha; Misra, Kuntal; Sahu, D K; Wang, Shan-Qin; Kumar, Brajesh; Li, Long; Anupama, G C; Dastidar, Raya; Elias-Rosa, N; Kumar, Brijesh; Singh, Mridweeka; Pandey, S B; et al.
ABSTRACT: We present the photometric and spectroscopic studies of a Type Ib SN 2015ap and a Type Ic SN 2016P. SN 2015ap is one of the bright ( M V = −18.04 mag) Type Ib while SN 2016P lies at an average value among the Type Ic SNe ( M V = −17.53 mag). Bolometric light-curve modelling of SNe 2015ap and 2016P indicates that both the SNe are powered by 56 Ni + magnetar model with 56 Ni masses of 0.01 and 0.002 M⊙, ejecta masses of 3.75 and 4.66 M⊙, spin period P 0 of 25.8 and 36.5 ms, and magnetic field B p of 28.39 × 10 14 and 35.3 × 10 14 G, respectively. The early spectra of SN 2015ap show prominent lines of He with a 'W' feature due to Fe complexes while other lines of Mg ii, Na i, and Si ii are present in both SNe 2015ap and 2016P. Nebular phase [O i ] profile indicates an asymmetric profile in SN 2015ap. The [O i ]/[Ca ii ] ratio and nebular spectral modelling of SN 2015ap hint towards a progenitor mass between 12 and 20 M⊙ .